Análise da qualidade do processo produtivo de concreto de uma empresa de pré-moldados na cidade de Pato Branco - PR - Marques, Janaína Santos Saldanha (2016)
It is known that concrete is one of the most employed materials on constructions. However, in order to attain the quality requirements both in the fresh and hardened state, it’s necessary to adopt procedures that guarantee the consistence of materials and processes. Besides, the structural elements are dimensioned based on the material’s characteristics, in other words, the concrete’s compressive strength (fck), steel’s tensile strength (fyk) and the combination of the most unfavourable actions. There are standards that the component materials of the concrete and the concrete itself have to reach, among them the ABNT NBR 12655 (2006) which deals with the preparation, control and receipt of the cement concrete portlant. Considering the need for the precast industry to meet the referred standards, this work’s main objective to determine the quality of the productive process of one of those companies, located in Pato Branco – PR. For that, the quantitative and qualitative analyses were used. The stage of quantitative analysis was done by determining the values of compressive strength at the age of 1 (one) day, 5 (five) days and 28 (twenty eight) days and by measuring the elastic modulus at the age of 28 (twenty eight) days. The stage of qualitative analysis was done through the formulation of an individual values’ graph showing the compressive strength of the concrete’s sample given by the volunteering company. With the results obtained it was possible to answer if the fck of the concrete produced met the fck requirement of the structural design. Through the analysis of the results the procedures used by the company, it was possible to suggest changes in production procedures of the concrete and dosage procedures of the concrete. Among the possible contributions it’s proposed the use of a new proportion of ingredients for the concrete, to be determined by the method of dosing from the Instituto de Pesquisas Tecnológicas (IPT), improve material control, and implament care during the concrete curing process.